VALIDATION OF THE PORTUGUESE VERSION OF THE ‘TEACHERS PERCEPTIONS ABOUT THE PROFESSION’ QUESTIONNAIRE - Batista, Paula; Sousa, Tiago; Amaral-da-Cunha, Mariana; Marques, Elisa (IJRDO- Journal of Educational Research, 2017)
The aim of this study is to validate the Portuguese version of the questionnaire developed by (Gilat, Kupferberg, & Sagee, 2006) and adapted by (Ezer, Gilat, & Sagee, 2010)), about the perceptions of preservice teachers in the training process experienced and its contribution to their professional life - Teachers Perceptions about the Profession (TPP). Two hundred and fourteen students completed the TPP questionnaire (98 females and 116 males, aged between 21 and 41). Feasibility of scale items was assessed by inspection of missing values (Dong & Peng, 2013). For exploration of factor structure, a principal component analysis (PCA) with varimax rotation was performed. Adequacy of the data for factor analysis was investigated with the KaiserMeyer-Olkin measure of sampling adequacy (KMO) and Bartlett’s test of sphericity (Field, 2009). Factors were extracted, using Kaiser’s criterion of retaining factors with eigenvalues of >1, and inspection of the scree plot (Cattell, 1966). Internal consistency reliabilities of the scale and its subscales (extracted factors) were assessed with Cronbach’s α. The results show that TPP questionnaire is a feasible, generally reliable, and valid instrument to assess perception of teacher education and professional identity among pre-service teachers